2003
DOI: 10.1016/s1525-0016(03)00210-7
|View full text |Cite
|
Sign up to set email alerts
|

Engraftment of retroviral EGFP-transduced bone marrow in mice prevents rejection of EGFP-transgenic skin grafts

Abstract: We have investigated whether a state of tolerance toward EGFP-expressing skin tissue can be induced by prior establishment of EGFP molecular chimerism by transplant of gene-transduced bone marrow in mice. Irradiated (10 Gy) C57BL/6J mice were transplanted with bone marrow cells transduced with two different retroviral vectors encoding EGFP. EGFP-transduced, mock-transduced, and age-matched control mice received skin grafts from both C57BL/6 EGFP-transgenic (B6-EGFP. Tg) and MHC-mismatched B10.A donor mice at 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 33 publications
2
30
0
3
Order By: Relevance
“…Approximately 30% eGFP chimerism was present in all recipients of eGFP transduced cells, although no assessment of tolerance was made. However, a study by Andersson et al 31 has recently shown that eGFP-transduction of BM delivered to irradiated recipients results in tolerance to eGFP-expressing skin grafts.…”
Section: Stem Cell Gene Delivery To Treat Hemophilia Bmentioning
confidence: 99%
“…Approximately 30% eGFP chimerism was present in all recipients of eGFP transduced cells, although no assessment of tolerance was made. However, a study by Andersson et al 31 has recently shown that eGFP-transduction of BM delivered to irradiated recipients results in tolerance to eGFP-expressing skin grafts.…”
Section: Stem Cell Gene Delivery To Treat Hemophilia Bmentioning
confidence: 99%
“…Enhanced green fluorescent protein (EGFP) is frequently used as a marker/model transgene in experimental genetherapy (bone marrow), transplantation and tumor models, and indeed, immune responses against EGFP can interfere in these models by clearing EGFP-expressing cells. [1][2][3][4] Conversely, the immunogenic potential of a transgene such as EGFP can be exploited to establish immunological tolerance or to induce deletion of EGFPspecific cytotoxic T cells by using EGFP-transduced hematopoietic cells 3,5 or splenic B cells, 4 thereby preventing rejection of gene-transduced cells/tissues. The immunogenicity of a transgene product is influenced by numerous factors such as the nature of the product, the vector, the target cell, the local microenvironment as well as the genetic and immunologic background of the host.…”
mentioning
confidence: 99%
“…2,3 Similar as in BALB/c mice, engrafting EGFP-transduced hematopoietic cells in C57BL/6 mice results in tolerance to EGFP-transgenic skin grafts. 3,5 Thus, although EGFP is clearly less immunogenic in C57BL/6 mice as compared with BALB/c mice, significant immune responses and tolerance to EGFP can be induced in C57BL/6 mice. This offers unique possibilities to study immunomodulatory strategies to less immunogenic transgene products in well-defined model systems.…”
mentioning
confidence: 99%
“…While the skin tissue of GFP-expressing B6 mice will be immune rejected when transplanted into GFP-negative B6 mice due to the expression of the immunogenic GFP minor antigen, 12,13 it is quite surprising that B6 iPSC-derived GFPexpressing skin tissue is completely immune tolerated by the GFP-negative B6 mice in this study. 11 Therefore, if using this chimeric mouse transplantation system, the B6 iPSC-derived skin cells will be immune tolerated by B6 mice even if they express minor antigens, making it an inappropriate assay to evaluate the immunogenicity of iPSC-derived cells.…”
Section: The Immunogenicity Of Ipsc-derived Tissues From Chimeric Micementioning
confidence: 79%